2018
DOI: 10.1111/nyas.13613
|View full text |Cite
|
Sign up to set email alerts
|

What does popular media have to tell us about the future of seafood?

Abstract: We examined ∼300 newspaper and business-oriented articles published over a 10-year period to assess trends in how seafood "sustainability" is talked about. We mapped key concepts relating to seafood sustainability as the word was used. We asked if the reports provided evidence that perceptions of problems or solutions for sustainability in seafood have changed over time. What were emergent areas of interest, and what concepts relevant to sustainable fisheries and seafood were absent in the reports? The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Private governance is governance driven by various types of non-state actors, who interact to produce institutional arrangements that structure and direct actors’ behavior in a particular domain [4]. The Marine Stewardship Council (MSC) and Fishery Improvement Projects (FIPs) are two models of private fisheries governance whose presence and influence has grown significantly in recent decades [5,6]. While the MSC is a private standards-setting body, FIPs are a template for improved fisheries governance, developed over time by multiple organizations (of which Sustainable Fisheries Partnership (www.sustainablefish.org) and World Wildlife Fund (www.worldwildlife.org) are the two most prominent, with the aim to make fisheries more sustainable by providing a strategic plan for actions that should lead to a change in policy or practices [7].…”
Section: Introductionmentioning
confidence: 99%
“…Private governance is governance driven by various types of non-state actors, who interact to produce institutional arrangements that structure and direct actors’ behavior in a particular domain [4]. The Marine Stewardship Council (MSC) and Fishery Improvement Projects (FIPs) are two models of private fisheries governance whose presence and influence has grown significantly in recent decades [5,6]. While the MSC is a private standards-setting body, FIPs are a template for improved fisheries governance, developed over time by multiple organizations (of which Sustainable Fisheries Partnership (www.sustainablefish.org) and World Wildlife Fund (www.worldwildlife.org) are the two most prominent, with the aim to make fisheries more sustainable by providing a strategic plan for actions that should lead to a change in policy or practices [7].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the linkage between social justice and seafood sustainability has not always been obvious. One analysis of several hundred popular media articles published from 2003-2013 dealing with sustainable seafood found that almost none were linking social issues with seafood sustainability (Van Holt et al, 2018). Among experts informing seafood certification processes, initial hesitation also existed due to the normative aspects of social justice and the lack of universally accepted external reference points for some social issues such as what constitutes fair pay or underage labor (Blasiak et al, 2017a).…”
Section: Labor Abusementioning
confidence: 99%
“…, 2021). Nonetheless, such labels are often discussed as both a problem and a solution in public debates and the media (Van Holt et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%